1988
DOI: 10.1152/jn.1988.59.3.796
|View full text |Cite
|
Sign up to set email alerts
|

Organization of the primate face motor cortex as revealed by intracortical microstimulation and electrophysiological identification of afferent inputs and corticobulbar projections

Abstract: 1. The technique of intracortical microstimulation (ICMS), supplemented by single-neuron recording, was used to carry out an extensive mapping of the face primary motor cortex. The ICMS study involved a total of 969 microelectrode penetrations carried out in 10 unanesthetized monkeys (Macaca fascicularis). 2. Monitoring of ICMS-evoked movements and associated electromyographic (EMG) activity revealed a general pattern of motor cortical organization. This was characterized by a representation of the facial musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
97
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(112 citation statements)
references
References 0 publications
15
97
0
Order By: Relevance
“…This ordered somatotopy with overlap is consistent with the findings in fMRI, ECoG, and microstimulation in primates. 1,9,21 Similarly, the probability map for speech arrest in the pars opercularis and precentral gyrus fits well with prior results. 18,22 There are a number of limitations to the present study that should be mentioned.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This ordered somatotopy with overlap is consistent with the findings in fMRI, ECoG, and microstimulation in primates. 1,9,21 Similarly, the probability map for speech arrest in the pars opercularis and precentral gyrus fits well with prior results. 18,22 There are a number of limitations to the present study that should be mentioned.…”
Section: Discussionsupporting
confidence: 82%
“…It seems likely that the spatial scale of clinical stimulation (5 mm) might result in movements closer to the tonic/seizure end of the spectrum, whereas microstimulation (~ 1 mm) may produce finer movements closer to the behavioral end of the spectrum. 8,9,16 Just as in previous human and animal stimulation studies, the observed responses were stereotyped across subjects, allowing for easy classification in most cases.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…9). This relationship is supported by studies examining the effects of cortical stimulation on the ventral region of M1 which primarily elicits contralateral lower facial movements (Penfield, 1937;Woolsey et al,1952;Woolsey et al, 1979;McGuinness et al, 1980;Huang et al, 1988;Triggs et al, 2005) and longstanding clinical observations which have drawn the association between prominent contralateral lower facial paresis and injury afflicting the lateral peri-central cortex of the cerebral hemisphere (Green, 1938;Symon et al, 1975;Brodal, 1981;Adams et al, 1997). However, it has also been shown that to a lesser extent, OO activation can occur following direct stimulation of M1 (Woolsey et al, 1979;Benecke et al, 1988;Cruccu et al, 1990;Roedel et al, 2001;Sohn et al, 2004;Paradiso et al, 2005) and deficits transpire in OO function following damage to M1 that are less notable than perioral deficits, but are nonetheless detectable (Kojima et al, 1997).…”
Section: Intranuclear Localization Of Oo Motor Neurons and Implicatiomentioning
confidence: 91%
“…We have recently begun investigating the possible role and plasticity of the face sensorimotor cortex in the monkey's acquisition of orofacial motor skills, building on our earlier findings from intracortical microstimulation (ICMS) mapping and recording of neuronal activity in the awake monkey's face MI. The mapping had revealed an extensive representation of the orofacial muscles participating in facial expression and other communicative behaviours as well as in cyclic jaw and tongue movements associated with ingestive behaviours (e.g., licking, mastication, swallowing; Huang et al 1988Huang et al , 1989Martin et al 1999). The cyclic movements can be evoked not only from face MI but also from cortical regions more lateral to face MI (e.g., the "cortical masticatory area," CMA).…”
Section: Great Ape Communication: Cognitive and Evolutionary Approachesmentioning
confidence: 99%